Conspicuous Consumption and Visible Inequality - Ana Ferrer; Francisco M. Gonzalez; Iuliia Nesterova (Institute of Labor Economics (IZA), 2025)
We document a significant effect of visible inequality on household spending in the United States from 2010 to 2018, but we do not find a comparable effect before the Great Recession. Our proposed definition of visible inequality refers to differences across households in their expenditures on highly noticeable consumption categories, including clothing, personal care, food away from home, and vehicles. Our empirical strategy exploits robust implications of a simple intertemporal model of conspicuous consumption, where a household's reference group consists of others in the same age group. Household spending is influenced by the distribution of permanent incomes within age groups, and visible inequality serves as a proxy for permanent income inequality. Our findings indicate that consumption externalities significantly distort household spending, which could have been up to 25 percent lower without these distortions. We hypothesize that low interest rates and social media contribute to these effects.
Keywords: D1; E21; 330; visible inequality; relative consumption; permanent income inequality